Effect of Plantar Pressure Training on Gait and Walking Ability in Hemiplegic Patients - Jiulong SU; Kui LI; Cuihuan PAN; Xingwang SONG; Maohua FAN; Zhengmao YE; Huikai SHAO (康复学报)
Objective:To investigate the effect of plantar pressure training on gait and walking ability in hemiplegic patients.Methods:Sixty hemiplegic patients were randomly allocated into plantar pressure training group (n=30) and rehabilitation treatment group (n=30). The rehabilitation treatment group received rehabilitation training based on Bobath and Motor Relearn Program, the plantar pressure training group received varied erect position stand and walking on the pressure platform, thirty minutes for each course, 5 courses a week for 3 weeks continuously. Frequency of stride, gait cycle, stride length, pace, step deviation, double support phase were measured before and after treatment by GaitWatch. Walking ability was measured by functional ambulation classification (FAC).Results:An increase of frequency of stride, gait cycle, stride length, pace, step deviation, double support phase was investigated in both groups after training (P<0.05), and the functional improvement of the plantar pressure training group was more significant when compared with the rehabilitation treatment group (P<0.05), but it was not significant difference in step deviation and FAC (P>0.05).Conclusion:Plantar pressure training can improve the patient's walking ability, effectively enhance the gait of hemiplegic patients.